My Aunt Margaret's Mirror - Scott, Walter, 1771-1832 (Salt Lake City, UT : Project Gutenberg, 1999)
"My Aunt Margaret's Mirror" by Walter Scott is a short story published in 1828. When Lady Jemima's husband vanishes after joining Marlborough's army in 1702, she seeks answers from a mysterious Italian doctor who claims supernatural powers. Through his enchanted mirror, she witnesses a shocking revelation about her absent spouse. What she sees will shatter her world and set in motion a tragedy involving betrayal, violence, and broken hearts that echoes across generations. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Keepsake_Stories
Waverley novel
Release date is 1999-03-01
Produced by An Anonymous Volunteer, and David Widger
Keywords: Scotland -- Social life and customs -- Fiction; Magic -- Fiction